Socio-Political Role of Sardar Abdul Hameed Khan Dasti: A Muslim Leader & President of All India Muslim League District Muzafargarh Pakistan Moement and after ward 1945-1958 (A Historical Analisis) - Bibi, Naseeba; Akhtar, Dr. Sohail; Yaseen, Saad (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Muzaffargarh District is geographically located between the two rivers Indus and Chenab. Unfortunately, the history of the district is almost silent before the freedom movement of Pakistan. However, the district produced many important personalities and they had played an important role in the freedom movement of Pakistan as Sardar Abdul Hameed Khan Dasti was one of them. Sardar Abdul Hameed Khan Dasti was known as the voice of the district Muzaffargarh during the freedom movement of Pakistan. He worked for the social uplift of the people in Muzaffargarh. Among his various social services, the formation Anjman-e-Islamia Muzaffargarh in 1920 was most remarkable achievement which was an important charity organization of Muzaffargarh. With social services he was also an important political leader and representative of Muzaffargarh District. He was appointed the president of the All India Muslim League of the District Muzaffargarh in 1944.After the emergence of Pakistan he also worked for the prosperity of the people in Muzaffargarh District. This paper will explore the socio-political contribution of Sardar Abdul Hameed Khan in Muzaffargarh District.